A new dynamic recrystallization mechanism in adiabatic shear band of an α/β dual phase titanium alloy: Composition redistribution. (1st January 2022) - Zhu, Xinjie; Fan, Qunbo; Wang, Duoduo; Gong, Haichao; Gao, Yu; Qian, Feng; Jin, Shenbao; Sha, Gang
Abstract: In this paper, the composition distribution characteristics in adiabatic shear bands (ASBs) of an α/β dual phase Ti-5.5Mo-7.2Al-4.5Zr-2.6Sn-2.1Cr alloy and its influence on dynamic recrystallization (DRX) were investigated via atomic probe tomography. The results showed that in the ASB transition region, a clear grain boundary (GB) in α/β interface was observed. However, in the ASB central region, a "fuzzy GB" was formed in α/β interface, and abundant dislocations accumulated in the "fuzzy GB". In addition, β stabilizing elements (Mo/Cr) became rather sparse in some local regions of β grains to form finer α grains, while in some regions of α grains, local β stabilizing elements were enriched to form finer β grains, thus separating the original grains into finer DRX grains. The unique composition distribution characteristics in α/β grains and α/β interface were defined as composition redistribution, which was the combined result of localized plastic deformation and adiabatic temperature rise. Graphical abstract: Image, graphical abstract